ANALISIS PENDAPATAN PETANI PADI PADA GAPOKTAN SUMBER MULYO DESA BANJARAN KECAMATAN BANGSRI, KABUPATEN JEPARA - Dinda Ayu Sekarnurani; Migie Handayani; Agus Setiadi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2018)
ABSTRACTThe purposes of this research were to find out  the amount of income  and the factors that influence the income of Gapoktan Sumber Mulyo’s farmers. This research was done on January until February of 2017 in Banjaran Village, Bangsri Sub-District, Jepara Regency. The research method that used was survey method by doing a direct interview based on the available questionaire. There were 80 farmers that were selected randomly to be the respondent sample of this research. The research’s results showed the average income of farmers was Rp 4.369.956,-. The average of monthly income was Rp 1.092.489,- which is lower than  regional minimum wage of Jepara District. Cultivation of rice done by farmers was considered as profitable bussiness because the average of profitability is higher than the loan interest at of Sumber Mulyo Cooperative. The factors which influence farmer’s income were cost of seed (X1) and cost of fertilizer (X2). Meanwhile, the cost of drug (X3) and labour (X4) were not factors that affect Gapoktan Sumber Mulyo farmers’ income. Keywords : Farmer’s Income, Paddy.